Implementasi Supervisi Akademik dengan Pendekatan Demokratis dalam Meningkatkan Profesionalisme Guru - Afifatun, Siti (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2022)
Implementation of academic supervision that is scheduled, periodically programmed, and carried out in accordance with appropriate principles and approaches, the impact is very extraordinary on improving teacher professionalism. Professional teachers, will have a very significant impact on improving the achievement and activeness of students who are demands in the 4.0 era that students must be able to think critically, be able to solve problems, be creative, be able to communicate well and be able to collaborate in living more competitive lives. This study, discusses the results of school action research that describes the professionalism of teachers in SMPN 1 Tanjungraja that is not optimal, describes the implementation of academic supervision with a democratic approach, and increasing teacher professionalism can be increased through supervision with a democratic approach. The results of the research cycles I and II of the six teachers as respondents, on average increased quite significantly with the results of an increase of 5.9%. For this reason, it is recommended that the principal conduct supervision on a democratic approach in a scheduled and programmed manner.